Variation in space use between sites, years and individuals for an endangered migratory shorebird has implications for coastal planning - Amanda Lilleyman; Amélie Corriveau; Stephen T. Garnett; Robert Bush; Jon Coleman; Richard Fuller; Roz Jessop; Ian Leiper; Grace Maglio; Gavin O'Brien; Damien Stanioch; Micha V. Jackson (Conservation Science and Practice)
Abstract Much of the annual cycle of threatened migratory shorebirds is spent in non‐breeding areas, but there have been few studies on how that habitat is used at fine‐scale. Tracking data from 13 endangered far eastern curlews at three Australian non‐breeding locations revealed that home range size and maximum daily displacement varied substantially among study areas and between years. Home range overlap also varied with tidal cycle, generally being lower at low than high tide, though there was considerable variability across time and between sites. Variation in site fidelity may indicate behavioral flexibility but may also suggest that resources critical to survival vary between years. If the latter is the case, protection of what appears to be critical habitat in 1 year may not be adequate in subsequent years, necessitating a precautionary approach to the conservation of habitat extent over the long term. For species like the far eastern curlew, which are exceptionally hard to capture and highly threatened, tracking data should be analyzed from as many perspectives as possible to justify the cost to both researchers and birds. In this study, use of tracking data previously analyzed to reveal migration routes has yielded important insights into their ecology and optimal management.